Seasonal occurrence and chemical management of postharvest fungal rot pathogens of mandarin orange (Citrus reticulata Blanco) - VERMA*, VIDYA SAGAR (Indian Phytopathology, 2008)
Ten fungal pathogens isolated from diseased mandarin orange (Citrus reticulata) fruits during the entire marketing period were Penicillium digitatum, P. italicum, P. chrysogenum, Aspergillus niger, A. flavus, Alternaria alternata, Absidia corymbifera, Fusarium moniliforme, Rhizopus stolonifer and Lasiodiplodia theobromae. The seasonal disease profile of mandarin orange fruit clearly marked two distinct peak periods of fungal rot spoilage. In the first peak, the major monthly fruit rottage loss was inflicted by green and blue mold rots caused by Penicillium digitatum (1.78-2.44%) and P. italicum (0.73-1.30%). The second peak period of fruit spoilage inflicted by Aspergillus niger was observed during the summer months of May (5.27%) and June (6.05%). The cumulative rottage losses during the entire marketing season were 34.30%. Post-inoculation chemical treatments were ineffective against the major fruit rot pathogens. Pre-inoculation treatments of thiabendazole (0.05%), benomyl (0.05%) and carbendazim (0.05%) were highly effective against green and blue mold rots caused by P. digitatum and P. italicum, respectively followed by salicylic acid (0.05%), sodium metabisulphite (0.5%) and borax (6%) while thiophanate methyl (0.25%) and borax (6%) were most effective against black mold rot caused by Aspergillus niger.